A polymorphism of the metabotropic glutamate receptor mGluR7 (GRM7) gene is associated with schizophrenia - Ohtsuki, Tsuyuka; Koga, Minori; Ishiguro, Hiroki; Horiuchi, Yasue; Arai, Makoto; Niizato, Kazuhiro; Itokawa, Masanari; Inada, Toshiya; Iwata, Nakao; Iritani, Shyuji; Ozaki, Norio; Kunugi, Hiroshi; et al. (Schizophrenia research, 2008)
Glutamate dysfunction has been implicated in the pathophysiology of schizophrenia. The metabotropic glutamate receptors (mGluRs) are G-protein-coupled receptors. GRM7, the gene that encodes mGluR7, is expressed in many regions of the human central nervous system. The GRM7 gene is located on human chromosome 3p26, which has been suggested by linkage analysis to contain a susceptibility locus for schizophrenia. We screened for mutations in all exons, exon/intron junctions, and promoter regions of the GRM7 gene in Japanese patients with schizophrenia and evaluated associations between the detected polymorphisms and schizophrenia. We examined the influence of one polymorphism associated with schizophrenia on the expression of GRM7 by dual-luciferase assay in transfected cells. Twenty-five polymorphisms/mutations were detected in GRM7. Case-control analysis revealed a potential association of a synonymous polymorphism (371T/C, rs3749380) in exon 1 with schizophrenia in our case-control study of 2293 Japanese patients with schizophrenia and 2382 Japanese control subjects (allelic p=0.009). Dual-luciferase assay revealed suppression of transcription activity by exon 1 containing this polymorphism and a statistically significant difference in the promoter activity between the T and C alleles. Our results support the possible association of a GRM7 gene polymorphism with genetic susceptibility to schizophrenia.